Digital Forensics Investigation on Proxmox Server Virtualization Using SNI 27037:2014 - Sudyana, Didik; Putra, Reza Tanujiwa; Soni, Soni (Sinkron : jurnal dan penelitian teknik informatika, 2019)
Server virtualization technology has experienced significant development so that more and more industries are adopting this technology. By using server virtualization, the industry can make savings in purchasing new servers and maintenance because virtualization allows one server to run with multiple operating systems at once. The high level of use of virtualization raises a gap for the occurrence of computer crimes involving virtualization. When computer crimes occur on virtualization, it is necessary to conduct digital forensic investigations to find useful clues in solving crime cases. Therefore, in this study a digital forensic investigation was conducted on Proxmox server virtualization by acquiring the entire storage virtualization media and carrying out checks on the results of the acquisition. Based on the investigation carried out, the acquisition technique by acquiring the entire storage media on Proxmox cannot be used because the structure of the evidence files and folders cannot be read perfectly